Multimedia Based Prayer Learning Application Designing Using Computer Assisted Instruction (CAI) Method - Pristiwanto Pristiwanto (Jurnal Ekspresi : Desain Komunikasi Visual dan Seni, 2023)
The use of media as a companion in the learning process is increasingly needed. The use of media is needed to overcome problems that arise in the learning process due to limited time, space, and objects. For this reason, a learning computer program was developed. Programs designed and developed for computer learning are adapted to existing media development models to be applied in learning. Learning to pray should be instilled in children from an early age. prayer is the weapon of the believer, a pillar of religion, nur in the sky and on earth. Prayers can prevent heinous and evil actions. Prayers can be assessed if they meet all the requirements and pillars. The obligation to perform prayers is the same as carrying out other obligations, according to Islamic law, it is determined for someone who has been seen as a legal subject or mukallaf (obligation to carry out Allah's regulations). Almighty God. Computer-Assisted Instruction (CAI) is a form of presenting learning materials and expertise or skills in small units, making it easy for students to learn and understand. Learning control in Computer-Based Learning is fully in the hands of students.